The Immunomodulatory Potential of Copper and Silver Based Self-Assembled Metal Organic Biohybrids Nanomaterials in Cancer Theranostics - Prajapati, Neela; Karan, Anik; Khezerlou, Elnaz; DeCoster, Mark A. (Frontiers in Chemistry, 2021)
Copper high aspect ratio structures (CuHARS) and silver cystine nanoparticles (AgCysNPs) are two unique micro/nano particles under study here that show extensive anti-cancer effects on a glioma tumor cell line. These micro/nano particles have shown potent toxicity in the presence of inflammatory stimulus (combination of tumor necrosis factor, [TNF] and lipo-polysaccharide, LPS). CuHARS with a concentration of 20 µg/ml uniquely increased the catalytic generation of nitric oxide (NO), an important contributor in the immune system. This NO was generated in a cell culture tumor microenvironment (TME) in the presence of 25 µM S-nitrosothiol (cysteine-NO) and the inflammatory stimulus. CuHARS increased the NO production by 68.75% when compared to untreated glioma cells with CysNO and inflammatory stimulus. The production of NO was significantly higher under similar circumstances in the case of normal primary structural cells like brain microvascular endothelial cells (BMVECs). The production of NO by BMVECs went up by 181.25% compared to glioma cells. This significant increase in the NO concentration could have added up to tumorigenesis but the anti-cancer effect of CuHARS was prominent enough to lower down the viability of glioma cells by approximately 20% and increased the metabolism of structural cells, BMVECs by approximately 200%. The immunomodulatory effect of NO in the TME under these circumstances in the presence of the novel micro/nano material, CuHARS has risen up compared to the effect of inflammatory stimulus alone and the potency specific nature of them towards tumor cells make it a suitable candidate for tumor treatment in early stages. Successive treatment of CuHARS to glioma cells also proved to be an effective approach considering the decrease in the total count of cells by 11.84 fold in case of 3 successive treatments compared to a single dose which only decreased the cell count by 2.45 fold showing the dose-dependent increasing toxicity towards glioma cells. AgCysNPs are another potent nanomaterial which also proved its significant toxic nature towards tumor cell lines as demonstrated here, but their immunomodulatory response is still unclear and needs to be explored further.